Clinical Characteristics of Pregnant Women With Coronavirus Disease 2019 in Wuhan, China. (11th July 2020) - Cheng, Biheng; Jiang, Tao; Zhang, Lu; Hu, Ruheng; Tian, Jinhua; Jiang, Yan; Huang, Bo; Li, Jun; Wei, Min; Yang, Jing; Ren, Shengxiang; Wang, Gaohua
Abstract: Background: Coronavirus disease 2019 (COVID-19) has become a pandemic. Despite the growing number of patients with COVID-19 infection, data on the clinical characteristics of pregnant patients are still limited. Methods: We retrospectively included childbearing-age female patients with laboratory-confirmed COVID-19 at Renmin Hospital of Wuhan University from January 15 to February 23, 2020. Demographic, clinical, radiological, laboratory, and treatment data were reviewed. Clinical characteristics of pregnant and nonpregnant patients were compared. Results: One hundred eleven childbearing-age women with COVID-19 were included, including 16 patients (14.4%) with severe or critical disease. Compared with nonpregnant patients (n = 80), pregnant patients (n = 31) were less likely to have dyspnea (16.1% vs 37.5%), asthenia (3.2% vs 33.8%), and ≥3 symptoms (22.6% vs 45.0%); had a significantly higher neutrophil count (5.2 vs 2.5 ×10 9 /L) and a higher percentage of CD3+ cells (76.7% vs 73.7%) and CD8+ cells (32.3% vs 28.4%); and had a dramatically lower percentage of lymphocytes (18.2% vs 31.8%), a lower CD4+/CD8+ ratio (1.2 vs 1.4), and a lower level of IgG (9.8 vs 11.9 g/L). Of note, pregnant patients had a significantly lower percentage of severe disease (3.2% vs 18.8%) and a substantially higher level of inflammation markers including neutrophil-to-lymphocyte ratio (4.4 vs 1.9) and systematic inflammatory index (812.8 vs 354.7) than nonpregnant patients. Seventeen live births were recorded, and all of these showed negative results of postnatal COVID-19 detection together with a normal Apgar score. Conclusions: Pregnant patients with COVID-19 had a lower level of severity and an enhanced inflammatory response and cell immunity when compared with nonpregnant patients.